Initial Screening of Thyroid Function Test in Premature and Term Infants at General Hospital Dr. Zainoel Abidin Banda Aceh - Pretyca Yudra Perdana; Dora Darussalam; Rusdi Andid; Mulya Safri; Syafruddin Haris; Nora Sovira (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Congenital hypothyroidism (CH) is the most common cause of mental retardation which can be prevented by early diagnosis and treatment. Premature infants have a higher risk of developing HK than term infants. Screening for CH in every newborn is important, however, in premature babies screening for CH using the TSH examination is often found to have normal levels in the first week of examination. This study is a cross sectional study where the research sample amounted to 62 infants who were divided into 2 groups, namely premature babies (n = 31) and term infants (n = 31). Statistical analysis used is Independent sample t test and Mann-Whitney U test. This study aims to assess the comparison of thyroid function (FT4 and TSHs) between premature infants and term infants at the first examination in the age range of 2 -6 days. The results showed that 90% (28/31) premature infants had hypothyroxinemia with lower FT4 levels than term infants (18.70 ± 6.50, 95% CI). TSHs levels in premature infants were higher than term infants (5.70 ± 5.27, 95% CI). This study concluded that FT4 is better at detecting thyroid function disorders in premature infants while TSHs are better at detecting abnormal thyroid function in term infants.